The payment order of antiquity and the Middle Ages : a legal history - Geva, Benjamin, 1946- (Hart monographs in transnational and international law, 2011)
Examining the legal history of the order to pay money initiating a funds transfer, the author tracks basic principles of modern law to those that governed the payment order of Antiquity and the Middle Ages. Exploring the legal nature of the payment order and its underpinning in light of contemporary institutions and payment mechanisms, the book traces the evolution of money, payment mechanisms and the law that governs them, from developments in Ancient Mesopotamia, Ancient Greece, Rome, and Greco-Roman Egypt, through medieval Europe and post-medieval England. Doctrine is examined in Jewish, Is.